Pig Organ Energy Loss Comparison Experiments Using BBs. Issue 3 (25th February 2016) - Maiden, Nicholas R.; Musgrave, Ian; Fisk, Wesley; Byard, Roger W.
Abstract: Torso models for ballistics research require that the mechanical properties of simulant materials must match the heterogeneous nature of tissues/organs within the human thorax/abdomen. A series of energy loss experiments were conducted on fresh porcine organs/tissues at room temperature and 37°C, using steel 4.5 mm BBs fired from a Daisy ® brand air rifle. They were compared to FBI and NATO specification ordnance gelatin and a candidate surrogate material called Simulant "A". Two CED M2 chronographs measured BB velocity. The resulting energy loss was established using KE = 1/2 mv² before and after target perforation. The combined results at room temperature and 37°C were as follows: FBI specification gelatin was similar ( p > 0.05) to heart and lung, spleen was similar to NATO specification gelatin, Simulant "A" was similar to hindquarter muscle, and hindquarter muscle, kidney, and spleen were similar to each other regarding energy retardation. These results can be used as a basis for the development of simulant materials to create an anatomically correct heterogeneous model.